Subjectively salient faces differ from emotional faces: ERP evidence - Anna Żochowska; Anna Nowicka (Scientific Reports, 2024)
Abstract The self-face is processed differently than emotional faces. A question arises whether other highly familiar and subjectively significant non-self faces (e.g. partner’s face) are also differentiated from emotional faces. The aim of this event-related potential (ERP) study was to investigate the neural correlates of personally-relevant faces (the self and a close-other’s) as well as emotionally positive (happy) and neutral faces. Participants were tasked with the simple detection of faces. Amplitudes of N170 were more negative in the right than in the left hemisphere and were not modulated by type of face. A similar pattern of N2 and P3 results for the self-face and close-other’s face was observed: they were associated with decreased N2 and increased P3 relative to happy and neutral faces. However, the self-face was preferentially processed also when compared to a close-other’s face as revealed by lower N2 and higher P3 amplitudes. Nonparametric cluster-based permutation tests showed an analogous pattern of results: significant clusters for the self-face compared with all other faces (close-other’s, happy, neutral) and for close-other’s face compared to happy and neutral faces. In summary, the self-face prioritization was observed, as indicated by significant differences between one’s own face and all other faces. Crucially, both types of personally-relevant faces differed from happy faces. These findings point to the pivotal role of subjective evaluation of the saliency factor.